2006
DOI: 10.1088/0953-8984/18/34/017
|View full text |Cite
|
Sign up to set email alerts
|

Study on the electrical and dielectric behaviour of Zn-substituted cobalt ferrialuminates

Abstract: The structural, electrical and dielectric properties of the spinel ferrite system ZnxCo1−xFeAlO4 (x = 0.2–0.5) have been studied by means of various experimental techniques. Polycrystalline samples of this series have been prepared by the double sintering ceramic method. The structural parameters such as the lattice constant, x-ray density, pore fraction, cation distribution, interionic distances and polaron radius have been determined for better understanding of the electrical and dielectric behaviour. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 48 publications
1
23
1
Order By: Relevance
“…Similar type of dispersion was observed by Mazen for Mg-Zn ferrites [23]. The essential condition for the formation of small polaron is that the polaron radius (R P ) should be less than the interionic distances [24]. Therefore an attempt has been made to calculate the polaron radius for all the compositions studied by the relation:…”
Section: Temperature Dependence Of Ac Conductivity ( Ac )supporting
confidence: 59%
“…Similar type of dispersion was observed by Mazen for Mg-Zn ferrites [23]. The essential condition for the formation of small polaron is that the polaron radius (R P ) should be less than the interionic distances [24]. Therefore an attempt has been made to calculate the polaron radius for all the compositions studied by the relation:…”
Section: Temperature Dependence Of Ac Conductivity ( Ac )supporting
confidence: 59%
“…The dielectric modulus is an electrical analogue to the dynamic mechanical shear modulus and is inversely related to the complex permittivity. 24 The dielectric modulus is represented as…”
Section: Resultsmentioning
confidence: 99%
“…4 it is observed that the lattice constant gradually increases from 8.37 Å to 8.41 Å with increasing Mn 2+ content, obeying Vegard's law [18]. Usually, in a solid solution of spinels within the miscibility range, a linear change in the lattice constant with the concentration of the components is observed [19,20]. This linear increase in lattice constant may be attributed to the replacement of smaller Co 2+ (0.78 Å) and Fe 3+ [22].…”
Section: Structural Analysismentioning
confidence: 99%